PENGEMBANGAN PENDIDIKAN KARAKTER: MEMBANGUN KEPRIBADIAN UNGGUL MELALUI PEMBELAJARAN - Sundari, Lea (YAYASAN PERCIKAN INSAN MANDIRI (PRISMA), 2024)
Character education is an important aspect in shaping the younger generation with noble character and noble character. This study aims to develop an effective learning model to instill character values in students. The research method used is qualitative research with a case study approach. The subjects of the study were students in grade X at SMAN 2 Sukabumi City. Data was collected through observation, interviews, and documentation. The results of the study show that an effective learning model in instilling character values is a project-based learning model. This learning model involves students actively in the learning process, so that they can better understand and internalize character values. This research contributes to the development of effective character learning models. Project-based learning models can be replicated and applied in other schools to help students build superior personalities.